The unknown Lenin : from the secret archive - Lenin, Vladimir Ilʹich, 1870-1924.; Pipes, Richard; Brandenberger, David; Fitzpatrick, Catherine A. (New Haven : Yale University Press, 1996)
Was Lenin a visionary whose ideals were subverted by his followers? Or was he a cynical misanthrope, even crueler than Stalin? This book, which contains newly released documents from the Lenin archive in Russia, lays bare Lenin the man and the politician, leaving little doubt that he was a ruthless and manipulative leader who used terror, subversion, and persecution to achieve his goals. Edited and introduced by the eminent scholar Richard Pipes, the documents date from 1886 through the end of Lenin's life. They reveal, among other things, that Lenin's purpose in invading Poland in 1920 was not merely to sovietize that country but to use it as a springboard for the invasion of Germany and England; Lenin took money from the Germans (here we have the first incontrovertible evidence for this); in 1919 Lenin issued instructions to the Communist authorities in the Ukraine not to accept Jews in the Soviet government of that republic; as late as 1922 Lenin believed in the imminence of social revolution in the West, and he planned subversion in Finland, Turkey, Lithuania, and other countries; Lenin had little regard for Trotsky's judgment on important matters and relied heavily on Stalin; Lenin assiduously tracked dissident intellectuals and urged repressive action or deportation; and Lenin launched a political offensive against the Orthodox Church, ordering that priests who resisted seizure of church property be shot - "the more the better."
Acknowledgments / Yury A. Buranov -- Political and Governmental Organizations -- Note on the Documents -- Introduction Lenin: A Biographical Sketch -- From the Secret Archive -- Patent of Nobility 12 December 1886 -- Transfer of Shmit Funds 21 February 1909 -- Draft Resolution November 1909 -- Shmit Legacy Receipt 13 November 1909 -- Telegram to Badaev 23 or 24 May 1914 -- Letter to Armand 7 June 1914 -- Letter to Armand Before 6 July 1914 -- Letter to Armand 16 July 1914 -- Letter to Armand Before 25 July 1914 -- Letter to Malinovsky 13 November 1915 -- Letter to Malinovsky 22 December 1915 -- Letter to Malinovsky 14 November 1916 -- Letter to Armand 26 November 1916 -- Letter to Armand 12 January 1917 -- Letter to Armand 19 January 1917 -- Letter to Armand 22 January 1917 -- Deposition About Malinovsky 8 June 1917 -- Remarks at Central Committee Meeting 15 November 1917 -- Message to Yuriev 26 March 1918 -- Exchange with Yuriev 9-10 April 1918 -- Exchange with Unidentified Person 5 June 1918 -- Cable About Ex-Tsar 16 July 1918 -- Conversation with Krasin 11 August 1918 -- Letter to Penza Communists 11 August 1918 -- Letter to Berzin 14 August 1918 -- Exchange with Chicherin 19 August 1918 -- Letter to Vorovsky 21 August 1918 -- Memo to Krestinsky 3 or 4 September 1918 -- Letter to Berzin 15-20 October 1918 -- Letter to Berzin 18 October 1918 -- Exchange with Kursky 26 November 1918 -- Telegram to Zinoviev 7 January 1919 -- Letter to Rozhkov 29 January 1919 -- Minutes of Eighth Congress 23 March 1919 -- Draft re Printers' Strike Before 28 April 1919 -- Trotsky's Exchange with Central Committee 5 July 1919 -- Note to Klinger 9 August 1919 -- Telegram to Frunze 30 August 1919 -- Memo from Trotsky 1 October 1919 -- Letter to Eliava 16 October 1919 -- Telegram to Zinoviev and Others 17 October 1919 -- Policy in the Ukraine Before 21 November 1919 -- Telegram to Stalin 14 February 1920 -- Telegram to Stalin 17 March 1920 -- Exchange with Chicherin 6 April 1920 -- Telegram to Atkarsk 20 April 1920 -- Note to Trotsky 7 May 1920 -- Notes on Finnish Communists 18 June 1920 -- Note to Politburo 24 June 1920 -- Telegram to Terek 25-30 June 1920 -- Letter from Chicherin 10 July 1920 -- Telegram to Unshlikht I 5 July 1920 -- Draft Resolution of RKP(b) Plenum Before 17 July 1920 -- Telegram to Stalin 23 July 1920 -- Telegram to Smilga 4 August 1920 -- Exchange on Armenia Before 9 August 1920 -- Note to Chicherin 21 August 1920 -- Draft of Politburo Resolution 21 August 1920 -- Report on Polish War 20 September 1920 -- Directives to Ioffe and Berzin 2 October 1920 -- Report on Pogroms 17-1 8 October 1920 -- Telegram to Stalin I 8 November 1920 -- Dzerzhinsky's Report on POWs November 1920 -- Resolution on Turkey Before 4 December 1920 -- Draft of Politburo Resolution 26 January 1921 -- Remarks at Tenth Congress 13 March 1921 -- Telegram to Tsaritsyn 25 March 1921 -- Exchange on Weapons Purchases 18 May 1921 -- Exchange with Litvinov 29 June 1921 -- Telegram to Siberia 2 July 1921 -- Report on Pogroms 6 July 1921 -- Note to Chicherin 25 July 1921 -- Telegram on Food Supply 30 July 1921 -- Letter to Chicherin 6 August 1921 -- Note to Molotov 23 August 1921 -- Letter to Berzin 8 September 1921 -- Note to Unshlikht 21 September 1921 -- Note from Trotsky 4 October 1921 -- Telegram to Tsaritsyn 4 October 1921 -- Remarks on Weapons Purchases 21 October 1921 -- Remarks About Kamenev I December 1921 -- Letter to Krestinsky 28 January 1922 -- Letter to Molotov 30 January 1922 -- Letter to Molotov 31 January 1922 -- Letter to Sokolnikov 4 February 1922 -- Letter to Stalin and Kamenev 4 February 1922 -- Note to Sokolnikov After 4 February 1922 -- Letter to Chicherin 10 February 1922 -- Request to Pharmacy I 3 February 1922 -- Note to Kamenev 20 February 1922 -- Exchange with Molotov 6-7 March 1922 -- Trotsky's Memorandum 10 March 1922 -- Exchange with Trotsky 11 and 12 March 1922 -- Letter on Events in Shuia 19 March 1922 -- Note to Gorbunov 21 March 1922 -- Exchange with Kamenev After 4 April 1922 -- Request to Pharmacy 6 April 1922 -- Telegram to Chicherin 17 April 1922 -- Telegram from Politburo 17 April 1922 -- Telegram to Chicherin 25 April 1922 -- Letter from Trotsky 28 April 1922 -- Letter to Stalin 19 May 1922 -- Note to Politburo 22 May 1922 -- Letter to Stalin 15 June 1922 -- Note to Stalin 7 July 1922 -- Note to Kamenev mid-July 1922 -- Letter to Stalin 17 July 1922 -- Letter to Stalin and Kamenev 28 August 1922 -- Letter to Stalin 11 September 1922 -- Note to Unshlikht 17 September 1922 -- Letter to Radek 28 October 1922 -- Note to Zinoviev October-December 1922 -- Letter to Stalin 13 December 1922 -- Afterword Appendix Memo from Marchlewski 26 October 1919 -- Telegram from Frunze 24 August 1920 -- Telegram from Artuzov November 1920 -- Telegrams from Trotsky 4 October 1921 -- Message from Chicherin 30 January 1922 -- Chicherin's First Telegram 15 April 1922 -- Chicherin's Second Telegram 15 April 1922 -- Resolution About Lenin 18 December 1922 -- Instructions After Lenin's Death 22 January 1924 -- List of Document and Illustration Credits -- Index.
Includes index.
Print version record.
JSTOR
Keywords: Lenin, Vladimir Ilʹich, -- 1870-1924 -- Archives; Lenin, -- 1870-1924 -- Archives; Lenin, Vladimir Ilʹich, -- 1870-1924; Lénine, Vladimir Iliitch, -- (1870-1924) -- Archives; Heads of state -- Soviet Union -- Archives; Soviet Union -- Politics and government -- 1917-1936 -- Sources; Chefs d'État -- URSS -- Archives; URSS -- Politique et gouvernement -- 1917-1936 -- Sources; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; Heads of state; Politics and government; Soviet Union; Communisme; Chefs d'État -- URSS -- Archives; URSS -- Politique et gouvernement -- 1917-1928 -- Sources; 1917-1936; Archives; Sources